2022
DOI: 10.1177/00111287221134518
|View full text |Cite
|
Sign up to set email alerts
|

Do Control, Peers, and Permissive Attitudes to Drugs Influence Drug Use Frequency in a Gendered Way?

Abstract: The dominant role of heroin in Chinese drug scenes has been gradually replaced by synthetic drugs since 2014. The gendered patterns of drug use have also changed with the transformation in drug consumption. Drawing upon survey data from 716 drug users detained in compulsory detoxification institutions, this study shows that permissive attitudes to drug use are a significant correlate of drug use frequency, and the correlation is much stronger among males than females. Neither self-control nor family attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
(120 reference statements)
1
0
0
Order By: Relevance
“…However, some male participants revealed that they were still capable of seeking short-term employment in the illegal market, such as being employed as keepers of brothels and pirated pornographic DVD stores. Our data echoes criminological literature that indicates the gender gap and segmentation in the illegal market (Nguyen et al, 2022; Shen & Winlow, 2014; Zhang, 2022). As income-generation ability is one of the age-graded life events that influence the cessation motivation of individuals with SUD, future research focusing on how the intersection of gender, age, and drug use influences illegal employment and the cessation motivation of individuals with SUD would be recommended.…”
Section: Discussionsupporting
confidence: 85%
“…However, some male participants revealed that they were still capable of seeking short-term employment in the illegal market, such as being employed as keepers of brothels and pirated pornographic DVD stores. Our data echoes criminological literature that indicates the gender gap and segmentation in the illegal market (Nguyen et al, 2022; Shen & Winlow, 2014; Zhang, 2022). As income-generation ability is one of the age-graded life events that influence the cessation motivation of individuals with SUD, future research focusing on how the intersection of gender, age, and drug use influences illegal employment and the cessation motivation of individuals with SUD would be recommended.…”
Section: Discussionsupporting
confidence: 85%